2019
DOI: 10.1038/s41598-019-52180-y
|View full text |Cite
|
Sign up to set email alerts
|

Acral malignant melanoma; emphasis on the primary metastasis and the usefulness of preoperative ultrasound for sentinel lymph node metastasis

Abstract: This study aimed to evaluate the most common primary metastatic location of acral malignant melanoma and to evaluate the usefulness of preoperative ultrasound for sentinel lymph node metastasis. Ninety-eight Korean acral malignant melanoma patients were enrolled. Acral malignant melanoma was present in 76 lower limbs and in 22 upper limbs. The most common origin location was the sole (33.7%). The most common location of primary metastasis was loco-regional recurrence (22/34, 64.7%). The sensitivity, specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Among different melanoma subtypes, acral melanoma (AM) is the most frequent in non-white populations, including Asians and Africans, and is responsible for the higher proportion of cases in countries with a lower incidence of melanoma overall [ 3 , 4 , 5 , 6 , 7 ]. AM differs from the other melanoma forms in the biological profile causing specific genetic/immunohistochemical features and related behaviors [ 8 , 9 , 10 , 11 , 12 ]: first, it is a non-UV-related tumor arising from the epithelium-associated melanocytes; second, it shows the early onset of major chromosomal rearrangements with gene copy number changes and multiple high-level amplifications (e.g., driver mutations in GNAQ, NF1, KIT TP53, PTEN, or RB1 genes, versus BRAF and NRAS of superficial spreading and nodular melanoma) [ 13 ]; third, it exhibits specific molecular findings (e.g., CCND1 overexpression , AURKA , and TERT) [ 14 ]; fourth, it is characterized by a rapid evolution and ability to metastasize and, thus, a poor prognosis [ 15 , 16 , 17 ]. This said, AM is also known for having a late diagnosis compared with other forms: the more reported underlying hypothesis emphasize the patients’ (and/or physicians’) reticence in examining this area and the difficulty of the differential diagnosis with acral nevi -with reported rates of misdiagnosis of 20%—despite dermoscopic examination [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among different melanoma subtypes, acral melanoma (AM) is the most frequent in non-white populations, including Asians and Africans, and is responsible for the higher proportion of cases in countries with a lower incidence of melanoma overall [ 3 , 4 , 5 , 6 , 7 ]. AM differs from the other melanoma forms in the biological profile causing specific genetic/immunohistochemical features and related behaviors [ 8 , 9 , 10 , 11 , 12 ]: first, it is a non-UV-related tumor arising from the epithelium-associated melanocytes; second, it shows the early onset of major chromosomal rearrangements with gene copy number changes and multiple high-level amplifications (e.g., driver mutations in GNAQ, NF1, KIT TP53, PTEN, or RB1 genes, versus BRAF and NRAS of superficial spreading and nodular melanoma) [ 13 ]; third, it exhibits specific molecular findings (e.g., CCND1 overexpression , AURKA , and TERT) [ 14 ]; fourth, it is characterized by a rapid evolution and ability to metastasize and, thus, a poor prognosis [ 15 , 16 , 17 ]. This said, AM is also known for having a late diagnosis compared with other forms: the more reported underlying hypothesis emphasize the patients’ (and/or physicians’) reticence in examining this area and the difficulty of the differential diagnosis with acral nevi -with reported rates of misdiagnosis of 20%—despite dermoscopic examination [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hand is also exposed to trauma but its location is less favorable. The main sites of AL melanoma metastases are the lungs, distant lymph nodes, scalp, contralateral limb, and liver (Kwon et al., 2019).…”
Section: Acral Lentiginous: the Most Uncommon Of The 4 Major Cmm Subtmentioning
confidence: 99%
“…The accuracy of this procedure is approximately 99% (19). Presently, several experts advocate SLNB for tumor stages Ib and II (30). Recent research has shown that the overall occurrence of positive SLNs in patients undergoing SLNB is approximately 15 -20%.…”
Section: Introductionmentioning
confidence: 99%